Effects of intradermal bradykinin after inhibition of angiotensin converting enzyme. Issue 6580 (2nd May 1987) - Ferner, R E; Simpson, J M; Rawlins, M D
Abstract : Inhibitors of angiotensin converting enzyme may cause angio-oedema. To see if this might be due to potentiation of the tissue effects of bradykinin the thickness of weals raised by intradermal injection of saline or 1, 3, or 10 micrograms bradykinin was measured before and three times after single doses of captopril, enalapril, or placebo. The mean thickness increased with increasing doses of bradykinin. It did not change with time after the administration of placebo or captopril but increased from 0.61 mm before enalapril to 1.12 mm two and a half hours and 1.06 mm five hours after enalapril was given. Five subjects flushed when given bradykinin after captopril and four after enalapril, but none flushed when given bradykinin after placebo. It is concluded that angiotensin converting enzyme inhibitors potentiate the effects of intradermal bradykinin in vivo and that this may partially explain why they cause angio-oedema in susceptible patients.